Digital competence of teachers and students in Yakutia: problems and prospects of e-learning during the pandemic - Sorochinsky, Maksim Anatolyevich (Educação, 2021)
Under self-isolation and quarantine measures during the COVID-19 pandemic in 2020, distance learning is urgent at every educational level. These events affected the digital competence of teachers and students of pedagogical specialties who teach students and schoolchildren. The article analyzes the digital competencies required for a modern teacher to successfully implement students’ educational needs when using distance educational technologies and e-learning. The research objective is to increase the level of digital competence by assessing this level and identifying problems in the e-learning usage. The study was carried out through a questionnaire developed by the National Agency for Financial Research (NAFR) analytical center Russian Teachers’ Digital Literacy, allowing identification of the main competencies required for a modern teacher, such as work in distance learning environments, knowledge of the basics of cloud technologies, and the ability to organize online and offline interaction, using various services. According to the calculation of Kendall’s concordance coefficient, a ranking of the plus and minus sides identified in the organization of remote interaction among teachers and students of the Republic of Sakha (Yakutia) during the pandemic was made. The study outcomes allowed increasing the efficiency of work with students and teachers and organizing refresher courses and support in the e-learning implementation